Senior design. - Goldberg, J. (IEEE Engineering in medicine and biology magazine)
Senior design courses teach students about the product development process, project management, and teamwork. These topics are typically taught by faculty through lectures and mentoring of project teams. In many senior design courses, representatives from industry are involved in teaching and mentoring activities. Industry involvement in senior design courses can provide many benefits to students, faculty, and academic institutions.